2021
DOI: 10.1002/ptr.7156
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TMPRSS4 mediated epithelial‐mesenchymal transition is critically involved in antimetastatic effect of melatonin in colorectal cancers

Abstract: In the current study, the underlying anti‐metastatic mechanism of melatonin contained in some edible plants was explored in association with transmembrane protease serine 4 (TMPRSS4) mediated metastasis and epithelial–mesenchymal transition (EMT) signaling in human HCT15 and SW620 colorectal cancer cells. Here, TMPRSS4 was highly expressed in HCT15, but was weakly expressed in SW620 cells. Melatonin exerted weak cytotoxicity, decreased invasion, adhesion, and migration, and attenuated the expression of TMPRSS4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The JNK pathway's involvement in oncogenic transformations and cell proliferation is well-documented across a diverse spectrum of cancer types [17,18]. This signaling pathway, which includes c-Jun N-terminal kinases (JNKs), plays a critical role in facilitating the uncontrolled growth of cancer cells and their transformation into malignant forms [19]. Its common presence in cancer tissues contributes to their aggressiveness and progression [20], making the JNK pathway a potential target for therapeutic interventions to curb tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The JNK pathway's involvement in oncogenic transformations and cell proliferation is well-documented across a diverse spectrum of cancer types [17,18]. This signaling pathway, which includes c-Jun N-terminal kinases (JNKs), plays a critical role in facilitating the uncontrolled growth of cancer cells and their transformation into malignant forms [19]. Its common presence in cancer tissues contributes to their aggressiveness and progression [20], making the JNK pathway a potential target for therapeutic interventions to curb tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that the melatonin treatment caused an increase in the ratio of E-cadherin/N-cadherin in tumor cells while suppressing Snail and MMP-9 levels [ 123 ]. Additionally, in vitro studies using human HCT15 and SW620 colorectal cancer cells showed that the melatonin treatment had a regulatory effect on E-cadherin and Snail-expression levels while exerting weak cytotoxicity [ 124 ]. Similar results were obtained in gallbladder cancer, showing an increase in epithelial markers (E-cadherin) and a decrease in mesenchymal markers (N-cadherin, vimentin and Snail), which seem to be related to the inhibition of the phosphorylation of ERK1/2 ultimately mediated by melatonin [ 125 ].…”
Section: Melatonin As An Inhibitor Of the Epithelial-to-mesenchymal T...mentioning
confidence: 99%
“…1 nM E-cadherin Snail [121] Breast cancer MCF-7 1 nM Twist1, Slug, Akt [129] Osteosarcoma MG-63 200 nM E-cadherin N-cadherin, Snail, MMP-9 [123] Colorrectal cancer HCT-15 SW620 1-2 mM E-cadherin Snail [124] Gallbladder cancer GBC-SD 0.1-2 mM E-cadherin N-cadherin, Snail, Vimentin [125] Non-small cell lung cancer H1299 0.1 mM Snail, Twist1 [126] Lung cancer A549, CL1-5 1 mM Twist1 [127] Lung cancer CL1-5 1 mM Slug, Twist1, β-catenin [128] Melatonin and EMT-related microRNAs. MicroRNAs are small noncoding RNA molecules that regulate gene expression at a post-transcriptional level.…”
Section: Melatonin As An Inhibitor Of the Epithelial-to-mesenchymal T...mentioning
confidence: 99%
“…Moreover, melatonin targets extracellular signal-regulated kinase 1/2 (ERK1/2)-mediated induction of EMT in gallbladder cancer cells [ 41 ]. Furthermore, melatonin downregulates the metastasis of colon cancer cells by inhibiting transmembrane protease and serine 4 (TMPRSS4)-mediated EMT [ 42 ].…”
Section: Anticancer Effect Of Melatoninmentioning
confidence: 99%